An overview of Historical Development of Swahili Translation in Tanzania - Sadiki Moshi Feruzi; Japhari Salum (Universitas Muhammadiyah Metro, 2022)
This paper aims at giving an overview of the historical development of Swahili translation in Tanzania. Currently, the available books and other publications have a little information on the history of Swahili translation. The data of this study was drawn through documentary review where books related to translation in Tanzania, dissertations and journal articles mostly published by reputable journals and indexed with world top data bases were thoroughly analysed. The findings demonstrate that before and during colonial period translation works were practiced informally and focused on serving one-time communication purpose. During post-colonial period translations by many writers occupied a large portion in the Tanzanian literary polysystem and in the 21st century translations have focused on economic, political and social cultural development of the country. The current trend in publications show that Swahili translation has increased and many scholars are attracted in the field. The study recommends further studies to be carried out in thematic focus of Swahili translations in pre-colonialism, during colonialism and post-colonialism as well.